Com’è profondo il mare Gli uominiche lo misurano, l’Istituto Idrografico della Marina - Nobili, Alessandro (GEOmedia, 2014)
Measuring sea depths: the Italian hydrographic Institute Since 1873 the Italian Hydrographic Institute (Istituto Idrografico della Marina - IIM) has been involved in sea depth measuring in order to improve safety of navigation. The main mission of the institute is to provide hydrographic services for waters of Italian national responsibility required by the International Convention for the Safety of Life at Sea (SOLAS). This role requires the coordination and determination of policy and standards which covers both hydrographic surveying and charting, as well as contributing to the coordination, exchange and standards related to geospatial data in general. IIM's traditions and methods take their origins from the pioneers of hydrography; in this paper the author briefl y describes the main stages in IIM's history, passing throught scientifi c and international activities and concludine with challenges and prospects of digital era.